Analisis Peran Profesi Guru dalam Meningkatkan Mutu Pendidikan di Era Milenial - Torimtubun, Hendrikus (Politeknik Kampar, 2024)
This study aligns to find out the Role of Teacher Profession in Improving the Quality of Education in the Millennial Era and to determine the quality of education that can be implemented in the Millennial Era. Qualitative approach with library research methods. The results of the study explain that teachers are a special profession that requires their own skills. The professionalism of the teacher in learning determines the direction of where the students are carved. They have the potential to form a future by providing education that not only provides knowledge, but to form individuals with strong moral values and social skills. Therefore, the role of teachers in education is more than just the delivery of information; it is a call to form a generation that is able to deal with challenges with courage, ethics, and a sense of responsibility.